Analysis of Blast Wave Propagation Inside Tunnel - 刘晶波 闫秋实 武俊 (Transactions of Tianjin University, 2008)
The explosion inside tunnel would generate blast wave which transmits through the longitudinal tunnel. Because of the close-in effects of the tunnel and the reflection by the confining tunnel structure, blast wave propagation inside tunnel is distinguished from that in air. When the explosion happens inside tunnel, the overpressure peak is higher than that of explosion happening in air. The continuance time of the blast wave also becomes longer. With the help of the numerical simulation finite element software LS-DYNA, a three-dimensional nonlinear dynamic simulation analysis for an explosion experiment inside tunnel was carried out. LS-DYNA is a fully integrated analysis program specifically designed for nonlinear dynamics and large strain problems. Compared with the experimental results, the simulation results have made the material parameters of numerical simulation model available. By using the model and the same material parameters, many results were adopted by calculating the model under different TNT explosion dynamites. Then the method of dimensional analysis was used for the simulation results. As overpressures of the explosion blast wave are the governing factor in the tunnel responses, a formula for the explosion blast wave overpressure at a certain distance from the detonation center point inside the tunnel was derived by using the dimensional analysis theory. By comparing the results computed by the formula with experimental results which were obtained before, the formula was proved to be very applicable at some instance. The research may be helpful to estimate rapidly the effect of internal explosion of tunnel on the structure.